Association of Cholecystectomy With Liver Fibrosis and Cirrhosis Among Adults in the USA: A Population-Based Propensity Score-Matched Study - Xie, Zhi-Qin; Li, Hong-Xia; Tan, Wen-Liang; Yang, Lei; Ma, Xiao-Wu; Li, Wen-Xin; Wang, Qing-Bin; Shang, Chang-Zhen; Chen, Ya-Jin (Frontiers in Medicine, 2021)
Background and Aims: Cholecystectomy is the “gold standard” for treating diseases of the gallbladder. In addition, non-alcoholic fatty liver disease (NAFLD), liver fibrosis or cirrhosis, are major causes of morbidity and mortality across the world. However, the association between cholecystectomy and these diseases is still unclear. We assessed the association among US adults and examined the possible risk factors. Methods: This cross-sectional study used data from 2017 to 2018 National Health and Nutrition Examination Survey, a population-based nationally representative sample of US. Liver fibrosis and cirrhosis were defined by median stiffness, which was assessed by transient elastography. Furthermore, patients who had undergone cholecystectomy were identified based on the questionnaire. In addition, Propensity Score Matching (PSM, 1:1) was performed based on gender, age, body mass index (BMI) and diabetes. Results: Of the 4,497 included participants, cholecystectomy was associated with 60.0% higher risk of liver fibrosis (OR:1.600;95% CI:1.278–2.002), and 73.3% higher risk of liver cirrhosis (OR:1.733, 95% CI:1.076–2.792). After PSM based on age, gender, BMI group and history of diabetes, cholecystectomy was associated with 139.3% higher risk of liver fibrosis (OR: 2.393;95% CI: 1.738–3.297), and 228.7% higher risk of liver cirrhosis (OR: 3.287, 95% CI: 1.496–7.218). Conclusions: The present study showed that cholecystectomy is positively associated with liver fibrosis and cirrhosis in US adults. The discovery of these risk factors therefore provides new insights on the prevention of NAFLD, liver fibrosis, and cirrhosis.